2020
DOI: 10.1016/j.psj.2020.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of breeder age on embryonic development, hatching results, chick quality, and growing performance of the slow-growing genotype

Abstract: The present study aimed to ascertain the effects of slow-growing breeder age on embryo development, incubation results, and chick quality and of the interaction between breeder age and hatching time on initial performance. A total of 630 hatching eggs obtained from a commercial flock of slow-growing broiler breeders (Isa Label Naked Neck) were evaluated in 2 experiments. The first experiment evaluated embryo development and hatching results for broiler breeder age treatments of 38 and 51 wk, whereas the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Higher hatchling (initial) weights from 60-wk-old breeders in this study can be attributed to heavier eggs being set during incubation. Additionally, the higher weight of the chicks from older breeders can be attributed to the higher yolk of the eggs ( Machado et al, 2020 ). The yolk sac is a crucial nutrient source during perinatal development.…”
Section: Discussionmentioning
confidence: 99%
“…Higher hatchling (initial) weights from 60-wk-old breeders in this study can be attributed to heavier eggs being set during incubation. Additionally, the higher weight of the chicks from older breeders can be attributed to the higher yolk of the eggs ( Machado et al, 2020 ). The yolk sac is a crucial nutrient source during perinatal development.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has expected that breeder age can affect intestinal development, that is, chicks from older breeders have longer villus in the duodenum, jejunum, and ileum and lower villus density compared to the chicks from young breeders (Maiorka et al, 2016; Yalcin et al, 2013). Comparing eggs from 38 and 51 weeks slow‐growing broiler breeders, Machado et al (2020) also found a greater developed intestinal villi. The more developed intestine obtained in day‐old chicks from older breeders is associated with the yolk absorption of developing embryos, which is higher in embryos of the older breeders than that of younger breeders (Nangsuay et al, 2011).…”
Section: Maternal Factors Affecting Intestine Developmentmentioning
confidence: 95%
“…Egg production from local purebreds is still a niche form of production, which shows variability in the management of birds throughout their growth and laying cycle and in the egg supply for marketing. Nonetheless, for dual-purpose breeds, the availability of chicks for meat production is a limitation for the management of the farm [12]. For birds reared outdoors, variations in the onset of laying and on the hen-day egg production may occur according to the month of hatching [13], as well as the age, which varies among genotypes [14].…”
Section: Introductionmentioning
confidence: 99%